A profile of the software industry : emergence, ascendance, risks, and rewards - Slaughter, Sandra A. (Industry profiles collection., 2014)
Software plays a critical role in today's global information economy. It runs the computers, networks, and devices that enable countless products and services. Software varies in size from vast enterprise and communications systems like SAP's enterprise resource planning system with hundreds of millions of lines of code to tiny apps like Angry Birds that run on mobile phones. Companies in the software industry produce and sell software products and related services. The industry is intensely competitive and has undergone a dramatic transformation from its roots in a handful of computer hardware mainframe producers in the 1960s to numerous large and small software companies today. Understanding how the software industry works and how the industry is evolving are important. Since software runs the computers and networks that support the flow of information in the global economy, the software industry also affects companies in all other industries that use these products and services for their own competitive advantage. This book offers a profile of the software industry and the companies in the industry. It describes the primary products and services produced in the industry; reviews the history of the industry; explains how the industry is structured; discusses its economics and competitive environment; and examines important trends and issues including globalization, workforce, regulation, and the emergence of new software business models.